Fall-out shelters for the human spirit : American art and the Cold War - Krenn, Michael L., 1957- (University of North Carolina Press, 2005)
A look at the successes, failures and controversies that arose when the US government and US art world sought to unite to make an international art program a reality between the 1940s and 1970s. It questions the cultural dimensions of US postwar diplomacy and asks how elements of the Cold War led to a redefinition of what is, and isn't, 'American'.